Punished by rewards : the trouble with gold stars, incentive plans, A's, praise, and other bribes - Kohn, Alfie (Boston : Houghton Mifflin Co., 1999)
Argues against the practice of offering people rewards in order to persuade them to get good grades, do good work, or behave in a certain manner, presenting evidence that shows the practice often has a negative effect, and discusses alternative methods of influencing behavior.
Includes bibliographical references (p. 377-411) and indexes.
Teacher Librarian.
Adult.
Adult
Keywords: Behaviorism (Psychology); Motivation (Psychology); Reward (Psychology); Behaviorism; Motivation (Psychology)